(untitled) (UNIZIK Journal of Educational Management and Policy, 2026)
This study examined components of professional development as predictors of academic staff research productivity in universities in Anambra State, Nigeria. Anchored on Human Capital Theory, the study adopted a correlational research design. The population comprised 3,276 academic staff from Nnamdi Azikiwe University and Chukwuemeka Odumegwu Ojukwu University, with a sample of 356 selected through multi-stage sampling. Data were collected using the Professional Development Questionnaire (PDQ) and Academic Staff Research Productivity Questionnaire (ASRPQ), and analysed using multiple regression and ANOVA. Findings revealed that professional development components research grants, fellowship programmes, sabbatical leave, workshops, and conference attendance jointly have a strong and significant predictive value (R = 0.846; R² = 0.715) on research productivity. Workshops and conferences were the strongest predictors. The study concluded that effective professional development programmes significantly enhance research productivity and recommended increased funding, strengthened fellowships, and greater participation in research-focused activities.